2013
DOI: 10.1111/1758-2229.12091
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of antagonistic effects on plant growth due to root co‐colonization by dark septate endophytes and ectomycorrhiza

Abstract: Dark septate endophytes (DSE) are very common root colonizers of woody plant species. Ascomycetes of the Phialocephala fortinii s.l.-Acephala applanata species complex (PAC) are the main representatives of DSE fungi in forest ecosystems. PAC and mycorrhizal fungi share the same habitat, but interactions among PAC, mycorrhizal fungi and plants are poorly understood. We compared the effects of single and dual inoculation of Norway spruce seedlings with PAC and the ectomycorrhizal (ECM) fungus Hebeloma crustulini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…Species of the PAC aggregate are reported to have different ecological roles, varying from mutualistic, plant nutrient uptake assisting (Haselwandter & Read, ; Jumpponen et al ., ; Jumpponen, ) to weak saprotrophic or pathogenic (Menkis et al ., ; Addy et al ., ; Lukešová et al ., ). Coexistence of endophytic PAC and mycorrhizal fungi in the plant roots is observed to enhance plant growth probably due to the release of nutrients from the soil by the PAC members (Reininger & Sieber, , ). In our study, members of PAC aggregate were detected from the roots and soils of all the plants studied while being generally more abundant in the P. sylvestris roots than in the soils or ericoid roots.…”
Section: Discussionmentioning
confidence: 99%
“…Species of the PAC aggregate are reported to have different ecological roles, varying from mutualistic, plant nutrient uptake assisting (Haselwandter & Read, ; Jumpponen et al ., ; Jumpponen, ) to weak saprotrophic or pathogenic (Menkis et al ., ; Addy et al ., ; Lukešová et al ., ). Coexistence of endophytic PAC and mycorrhizal fungi in the plant roots is observed to enhance plant growth probably due to the release of nutrients from the soil by the PAC members (Reininger & Sieber, , ). In our study, members of PAC aggregate were detected from the roots and soils of all the plants studied while being generally more abundant in the P. sylvestris roots than in the soils or ericoid roots.…”
Section: Discussionmentioning
confidence: 99%
“…Although the diversity of mycorrhizal fungi has been touted as critical to plant productivity (van der Heijden et al ., ; Hiiesalu et al ., ), this is likely to be most important in mixed plant communities, in which different species associate preferentially with specific mycorrhizal fungi. Reininger and Sieber () showed that co‐inoculation of plants with dark septate endophyte fungi limited reductions in plant growth caused by single inoculants, although an increased number of EM species has been shown to decrease plant biomass (Kennedy et al ., ). In the case of plant growth, the presence of multiple fungi could allow plants to invest only in productive associations, reducing the amount of cheating fungi in the rhizosphere, as has been shown for AM fungi (Kiers et al ., ; Wyatt et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have considered the link between antagonisms between symbionts and their combined effects on host growth [6]. Reininger et al [10] reported that dual inoculation of AMF and dark septate endophytes neutralized plant growth depression caused by endophyte colonization and that this might be attributed to a reduction of endophyte concentration by AMF colonization. This is consistent with the synergistic promotion of plant biomass caused by dual colonization of rhizospheric Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%